Ultra-thin materials for electrocatalytic CO2 reduction to prepare liquid fuels - WANG Yuchao; LI Qian; ZENG Jian; TANG Shuaihao; ZHENG Huanran; XU Liang; CHEN Zhiyan; LEI Yongpeng (Cailiao gongcheng, 2022)
The electrocatalytic CO2 reduction reaction (CO2RR) can not only alleviate the negative effects caused by excessive CO2, but also produce the carbon-containing fuels to alleviate energy shortages. However, the reactive paths of CO2RR are relatively complicated, and the problems such as low selectivity, low current density and poor stability exist. It is urgent to develop efficient and inexpensive catalysts to promote its development. Ultra-thin materials have the advantages of large specific surface area, fully exposed active sites, accelerated kinetic mass transfer, and adjustable electronic structure. They are expected to break the bottleneck of CO2RR, thus receiving widespread attention. Here, the synthesis and application of ultra-thin materials in the past four years in electrocatalytic CO2RR to produce liquid fuels (formic acid, methanol, acetic acid) were briefly summarized. The advantages of ultra-thin materials over bulk materials and their influence on catalytic activity, selectivity and reaction paths were discussed. Also, some suggestions for future development trends, including the synthesis methodology of ultra-thin materials, their potential as supports, mechanism analysis and machine learning were put forward.